Vietnam’s Labour Law from the Perspective of the Comprehensive and Progressive Agreement for Trans-Pacific Partnership - Hoai Thu, Le Thi (VNU Journal of Science: Legal Studies; Vol 35 No 3, 2019)
The ratification of the Comprehensive and Progressive Agreement for Trans-Pacific Partnership (CPTPP) is a chance for the economic development of Vietnam. Also, this Agreement creates demand on legal amendment, including legal regulations on labour. This article shall focus on analyzing commitments of state members on the labour issue in this Agreement, then comparing them with national regulations for estimating the compatibility between them and providing some proposals for improving such compatibility.